Novel RGD-lipid conjugate-modified liposomes for enhancing siRNA delivery in human retinal pigment epithelial cells - Chen CW (Dove Medical Press, 2011)
Cheng-Wei Chen1, Da-Wen Lu2, Ming-Kung Yeh3, Chia-Yang Shiau4, Chiao-Hsi Chiang1,5 1Graduate Institute of Life Sciences, 2Department of Ophthalmology, Tri-Service General Hospital, 3Institution of Preventive Medicine, 4Graduate Institute of Medical Sciences, 5School of Pharmacy, National Defense Medical Center, Neihu, Taipei, Taiwan Background: Human retinal pigment epithelial cells are promising target sites for small interfering RNA (siRNA) that might be used for the prevention and/or treatment of choroidal neovascularization by inhibiting the expression of angiogenic factor; for example, by downregulating expression of the vascular endothelial growth factor gene. Methods: A novel functional lipid, DSPE-PEG-RGD, a Arg(R)-Gly(G)-Asp(D) motif peptide conjugated to 1, 2-distearoyl-sn-glycero-3-phosphoethanolamine- N-[maleimide (polyethylene glycol)-2000], was synthesized for the preparation of siRNA-loaded RGD-PEGylated liposomes to enhance uptake of encapsulated siRNA in retinal pigment epithelial cells. Various liposomes, with 1 mol% and 5 mol% PEGylated lipid or 1 mol% and 5 mol% RGD-PEGylated lipid, were fabricated. Results: Characterization of the liposomes, including siRNA entrapment efficiency, average particle size and ζ-potential, were determined to be as follows: >96%, 129.7 ± 51 to 230.7 ± 60.7 nm, and 17.3 ± 0.6 to 32 ± 1.3 mV, respectively. For the in vitro retinal pigment epithelial cell studies, the RGD-PEGylated liposomes had high delivery efficiency with siRNA delivery, about a four-fold increase compared with the PEGylated liposomes. Comparison of the various liposomes showed that the 1 mol% RGD-modified liposome had less cytotoxicity and higher siRNA delivery efficiency than the other liposomes. The antibody blocking assay confirmed that uptake of the 1 mol% RGD-PEGylated liposome was via integrin receptor-mediated endocytosis in retinal pigment epithelial cells. Conclusion: The results of this study suggest that RGD-PEGylated liposomes might be useful for siRNA delivery into retinal pigment epithelial cells by integrin receptor-medicated endocytosis. Keywords: Arg-Gly-Asp, RGD, small interfering RNA, liposome, retinal pigment epithelial cells